Are jet ubiquitous in ULXs?. Issue Volume 10:Issue S313(2014) (24th March 2015) - Wolter, A.; Ghisellini, G.; Costamante, L.; Pintore, F.
Abstract: A jet model represents well different X-ray states of the bright ULX IC342 X-1.